Perceptions of medical students about the teaching of professionalism: a quantitative-qualitative study (Research, Society and Development, 2022)
Objective: Professionalism, a central theme in medical education and patient care, involves more than just knowledge of the profession's standards of competence. However, the hidden forms of teaching involve the risk of not being consciously assimilated by the students. Recognizing the perception of teaching and learning in medical education can provide changes in the approach to this construct. Methodology: This is a cross-sectional, analytical, observational study with a quantitative and qualitative approach. A questionnaire was applied on the perception of the importance of teaching professionalism, in addition to demographic data. Results: A total of 112 students participated in the study. As for the opportunities for teaching professionalism, most (55.4%) think it is possible to be taught about medical professionalism in “all modules”, but only 9.8% reported having learned about professionalism in all opportunities. Conclusion: It is noticed that, despite the recognized importance of teaching the subject for excellence in medical training, there is a perception that teaching-learning opportunities are lost.